KARTEL YANG DILAKUKAN OLEH MASKAPAI PENERBANGAN(STUDI PUTUSAN KPPU NOMOR : 15/KPPU-I/2019) - Nur Sulistiono, (2021)
The discussion in this study discusses the problem of the form of cartel actions carried out by the Reported Parties in the KPPU's Decision Number: 15/KPPU-I/2019. Another problem is the consideration of the Commission Council in deciding Case Number: 15/KPPU-I/2019. The case regarding the cartel contained in the KPPU's Decision Number: 15/KPPU-I/2019 which was carried out jointly by PT Garuda Indonesia (Persero), Tbk, PT Citilink Indonesia, PT Sriwijaya Air, PT NAM Air, PT Batik Air, PT Lion Mentari, and PT Wings Abadi. The Reported Parties are alleged to have violated the provisions of Article 5 and Article 11 of Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition by increasing the price of airline tickets. The data collection technique in this research is using the library research method. While the analysis technique carried out on the legal materials that have been collected by the author will be done deductively. The results of the study indicate that KPPU is only an administrative institution, so that KPPU can only impose administrative sanctions and is not authorized to impose criminal sanctions or civil sanctions. The KPPU Assembly has also decided that the business actors are guilty, but the KPPU Assembly has not imposed any sanctions on the mistakes of the business actors. The absence of sanctions imposed on cartel actors can make the perpetrators repeat their actions and in this case consumers will be harmed again.